Membangun Minat Siswa dalam Pembelajaran Sejarah Kebudayaan Islam Melalui Strategi dan Metode Modul Ajar yang Kreatif - M. Khair; Noor Azmah Hidayati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This article discusses the importance of building students' interest in learning Islamic Cultural History (SKI), which is often considered less interesting due to monotonous conventional methods. The research aims to explore creative and innovative learning strategies that can increase students' interest in SKI. Using qualitative descriptive methods and literature studies, researchers analyzed the relevance of learning interests and the development of interesting teaching modules. The findings show that teaching modules that integrate visual media and interactive technology can increase the attractiveness of learning, creating active and relevant learning experiences for students. Apart from that, the teacher's role is very crucial in using a variety of methods and providing constructive feedback. The implications of this research emphasize the need for a more creative approach in education to not only convey historical knowledge, but also shape students' character and identity. In this way, it is hoped that SKI learning will be more meaningful and help students understand cultural heritage in the context of modern life.